2023
DOI: 10.3389/fnins.2023.1102573
|View full text |Cite
|
Sign up to set email alerts
|

Association between DRD2/ANKK1 rs1800497 C > T polymorphism and post-traumatic stress disorder susceptibility: a multivariate meta-analysis

Abstract: BackgroundPrevious studies have suggested that the DRD2/ANKK1 rs1800497 C > T polymorphism plays a critical role in the risk of post-traumatic stress disorder (PTSD). However, published data are inconsistent or even contradictory. Therefore, we conducted a meta-analysis to explore the underlying correlation between the rs1800497 C > T polymorphism and PTSD risk.Materials and methodsA total of five online databases were searched, and all related studies were reviewed up to 1 October 2022. Critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Our results also revealed that the most highly significantly downregulated gene by methylone was Ankyrin Repeat and Kinase Domain Containing 1 (Ankk1), which regulates dopamine synthesis and has been associated with PTSD susceptibility ( Niu et al, 2023 ).…”
Section: Resultsmentioning
confidence: 68%
“…Our results also revealed that the most highly significantly downregulated gene by methylone was Ankyrin Repeat and Kinase Domain Containing 1 (Ankk1), which regulates dopamine synthesis and has been associated with PTSD susceptibility ( Niu et al, 2023 ).…”
Section: Resultsmentioning
confidence: 68%
“…This polymorphism has been associated with the regulation of dopamine synthesis and reduced D2 receptor expression in the brain, which forms the pathophysiological basis for various PTSD symptoms. The rs1800497 polymorphism has been shown to contribute to the severity of PTSD symptoms, and individuals with the A1 allele are more likely to develop PTSD following trauma exposure [ 42 ].…”
Section: Catalytic Factors Associated With Ptsdmentioning
confidence: 99%
“…It has been demonstrated that rs1800497 influences striatal D2 receptor availability [30] and DRD2 expression [31], but ANKK1 itself may function in dopaminergic pathways [32]. Rs1800497 T is reported to be a risk allele for mood disorders, addictions, and post-traumatic stress disorder (PTSD) [33,34].…”
Section: Introductionmentioning
confidence: 99%